Vicoa gokhalei (Inuleae, Asteraceae), a new species from the northern Western Ghats, India - Gosavi, Kumar Vinod Chhotupuri; Madhav, Nilesh Appaso; Chandore, Arun Nivrutti; Kambale, Sharad Suresh; Yadav, Shrirang Ramchandra (Phytotaxa, 2020)
A new species of Vicoa, V. gokhalei is described and illustrated from high elevated areas of northern Western Ghats, India. The new species is closely related with V. cernua which is also known from high elevated areas of northern Western Ghats. Along with detailed description, diagnostic characters, phenology, coloured photographs, illustration, ecological note, distribution and identity of the new species and key of Vicoa species for India are provided.